2006
DOI: 10.1111/j.1365-2036.2006.02785.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of chronic hepatitis C patients with sustained virological response to various forms of interferon‐based anti‐viral therapy

Abstract: SUMMARY BackgroundCombination anti-viral therapy achieves a sustained virological response (defined as HCV-RNA negativity 6 months after the end of therapy) of 56% of patients with chronic hepatitis C. Little is known about long-term durability of HCV-RNA negativity in patient treated with pegylated interferon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 36 publications
(50 reference statements)
6
54
0
2
Order By: Relevance
“…Only in seven patients (<1%), HCV-RNA was detected (after 391-1076 days of treatment). All these data indicate that the late relapse after SVR in chronic hrpatits C patients following an IFN-based anti-viral therapy is rare [16][17][18][19] . This is the first study from Bangladesh on longterm outcomes of anti-viral therapy for chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Only in seven patients (<1%), HCV-RNA was detected (after 391-1076 days of treatment). All these data indicate that the late relapse after SVR in chronic hrpatits C patients following an IFN-based anti-viral therapy is rare [16][17][18][19] . This is the first study from Bangladesh on longterm outcomes of anti-viral therapy for chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,6 Studies have demonstrated that SVR is associated with histological improvement, assessed by liver biopsy, and with the prevention of complications, such as the development of liver cirrhosis and HCC. [11][12][13][14] Thus, SVR as result of therapy is deemed as an important factor for long-term favourable prognosis, although 4.0% to 8.7% of late recurrence was observed in two studies. Ferreira, Carneiro, Souza et al In addition, some clinical studies have indicated the occurrence of HCC cases in cirrhotic patients who had developed SVR after antiviral treatment, emphasizing the need to maintain HCC screening regardless of treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, patients having prior appropriate treatment for HCC and no evidence of viable HCC at the start of antiviral therapy were enrolled. Patients with other liver disease such as chronic hepatitis B, a history of alcohol ingestion (≥30 g/day), human immunodeficiency virus infection, or obesity (body mass index ≥27 kg/m 2 of human recombinant erythropoietin (rEPO; Eprex ; Janssen Korea, Seoul, Korea) was given twice a week subcutaneously when absolute neutrophil count decreased to less than 500/mm 3 or hemoglobin level decreased to less than 8.0 g/dL, by the physician's discretion.…”
Section: Patientsmentioning
confidence: 99%
“…[2][3][4] Although treatment outcomes have evolved greatly since combination therapy was introduced to treat CHC, 5-7 antiviral treatment in patients with CHC-related HCC has rarely been reported. This study was aimed to evaluate the efficacy and safety of antiviral therapy in CHC patients after treatment for HCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation